GSK-3 Represses Growth Factor-inducible Genes by Inhibiting NF-κB in Quiescent Cells - Graham, Julie R. (American Society for Biochemistry and Molecular Biology, 2010)
GSK-3 is active in the absence of growth factor stimulation and generally acts to induce apoptosis or inhibit cell proliferation. We previously identified a subset of growth factor-inducible genes that can also be induced in quiescent T98G cells solely by inhibition of GSK-3 in the absence of growth factor stimulation. Computational predictions verified by chromatin immunoprecipitation assays identified NF-κB binding sites in the upstream regions of 75% of the genes regulated by GSK-3. p50 bound to most of these sites in quiescent cells, and for one-third of the genes, binding of p65 to the predicted sites increased upon inhibition of GSK-3. The functional role of p65 in gene induction following inhibition of GSK-3 was demonstrated by RNA interference experiments. Furthermore, inhibition of GSK-3 in quiescent cells resulted in activation of IκB kinase, leading to phosphorylation and degradation of IκBα and nuclear translocation of p65 and p50. Taken together, these results indicate that the high levels of GSK-3 activity in quiescent cells repress gene expression by negatively regulating NF-κB through inhibition of IκB kinase. This inhibition of NF-κB is consistent with the role of GSK-3 in the induction of apoptosis or cell cycle arrest in cells deprived of growth factors.